Family Firms, Alliance Governance and Mutual Knowledge Creation - Ricarda B. Bouncken; Mathew Hughes; Martin Ratzmann; Beate Cesinger; Robin Pesch (British Journal of Management, 2020)
For family firms, alliances represent a form of heightened entrepreneurial risk-taking. However, a dearth of research exists on the implications of forms of alliance governance for family firms. In a study of 939 non-equity alliances of family and non-family firms, we analyse how contracts and trust influence mutual knowledge creation. Both contract completeness and trust assist non-family firms in knowledge creation. However, family firms rely on high levels of trust for the creation of knowledge. Knowledge creation suffers when family firms encounter very complete contracts tied to attempts at high levels of trust. The negative interaction effect is especially strong for non-owner-run family firms.
Keywords: 650